2022
DOI: 10.1002/fsn3.3024
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of edible cricket flour to quality parameters and sensory characteristics of wheat bread

Abstract: This study evaluated the influence of edible cricket flour (ECF) on the quality parameters and sensory characteristics of wheat bread (WB), including the formation of volatile compounds (VC) and their relationship with emotions (EM) induced for consumers. ECF reduced dough pH, redness, and yellowness. At 5%, ECF increased the porosity of WB (by 7.87%). The quantity of ECF significantly affected WB's specific volume (p = .030), porosity (p = .0001), shape coefficient (p = .0001), and mass loss (p = .023). All W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…Face Reader™ has also been applied to evaluate the emotional response of consumers toward bread incorporating cricket flour (Bartkiene et al., 2022), although it provided some contradicting results. For instance, the sample with the highest content of cricket flour was associated with both “Happy” and “Sad” emotions, and the control sample elicited “Disgusted” emotions as frequently as the sample with the highest content of cricket flour.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Face Reader™ has also been applied to evaluate the emotional response of consumers toward bread incorporating cricket flour (Bartkiene et al., 2022), although it provided some contradicting results. For instance, the sample with the highest content of cricket flour was associated with both “Happy” and “Sad” emotions, and the control sample elicited “Disgusted” emotions as frequently as the sample with the highest content of cricket flour.…”
Section: Resultsmentioning
confidence: 99%
“…First, both Bartkowicz and Babicz-Zielinska (2020) and Ribeiro et al (2019) reported that the incorporation of edible insects led to a decrease in the association with characteristic and positive product attributes. Another common effect of insect incorporation is an increase in overall flavor/taste intensity, as well as the association with a prolonged aftertaste (Bartkiene et al, 2022;Biró et al, 2020;Ribeiro et al, 2019;Ribeiro et al, 2022a). Additionally, several negative flavor/taste attributes have been associated with insect incorporation: unpleasant aftertaste, soap (Ribeiro et al, 2019), rancid (Ribeiro et al, 2019;Ribeiro et al, 2022a), feed (Ribeiro et al, 2022a), fishy (Biró et al, 2020), bitterness (Bartkiene et al, 2022;Wendin et al, 2021), acidity (Wendin et al, 2021), and earthy/mushroom (Ribeiro et al, 2019;Wendin et al, 2021).…”
Section: Bakery and Snacksmentioning
confidence: 99%
See 2 more Smart Citations
“…The color coordinates of the lentil samples were evaluated on the surface using the CIE L*a*b* system (CromaMeter CR-400, Konica Minolta, Marunouchi, Tokyo Japan). The LAB viable counts were determined according to the method described by Bartkiene et al ( 22 ).…”
Section: Methodsmentioning
confidence: 99%